Evaluating content writing for the creative industry course from lecturers’ and students’ views - Susan Santika; Gin Gin Gustine; Tri Indri Hardini (Curricula: Journal of Curriculum Development, 2025)
In response to the increasing demand for English content writing in the creative industry, especially among university graduates working as bilingual content writers, this study evaluates the Content Writing for Creative Industry course organized by one of the English education study programs at a public university in Bandung through the English for Specific Purposes (ESP) approach. The study aimed to explore how lecturers, as syllabus designers, developed the course syllabus and to examine the views of students and lecturers, including practicing lecturers, on its implementation. Using Ellis' evaluation model, this qualitative study analyzed the 14-week course through a combination of syllabus reviews, student portfolios, questionnaires, interviews, and focus group discussions. Findings showed that students responded positively and recognized the alignment of course activities with tasks required in the creative industries. Students also expressed the need for more in-depth discussions on visual elements to increase audience engagement in the content. Meanwhile, lecturers, including practitioner lecturers, emphasized the importance of in-depth research by students in content planning, as well as the need for more comprehensive coverage of storytelling to engage audiences better.   Abstrak Sebagai respons terhadap meningkatnya permintaan akan penulisan konten berbahasa Inggris di industri kreatif, khususnya di kalangan lulusan universitas yang bekerja sebagai penulis konten dwi Bahasa, studi ini mengevaluasi mata kuliah Content Writing for Creative Industry yang diselenggarakan oleh salah satu program studi pendidikan bahasa Inggris di sebuah universitas negeri di Bandung melalui pendekatan English for Specific Purposes (ESP). Studi ini bertujuan untuk mengeksplorasi bagaimana dosen, sebagai perancang silabus, mengembangkan silabus mata kuliah tersebut serta menelaah pandangan mahasiswa dan dosen, termasuk dosen praktisi, terhadap implementasinya. Dengan menggunakan model evaluasi dari Ellis, studi kualitatif ini menganalisis mata kuliah selama 14 minggu melalui telaah silabus, portofolio mahasiswa, kuesioner, wawancara, dan diskusi kelompok terfokus. Temuan menunjukkan bahwa mahasiswa merespons secara positif dan mengakui keselarasan aktivitas perkuliahan dengan tugas-tugas diperlukan di industri kreatif. Mahasiswa juga mengungkapkan perlunya diskusi yang lebih mendalam mengenai elemen visual untuk meningkatkan keterlibatan audiens dalam konten. Sementara itu, para dosen, termasuk dosen praktisi, menekankan pentingnya riset mendalam oleh mahasiswa dalam perencanaan konten serta perlunya cakupan yang lebih komprehensif terkait storytelling supaya dapat lebih menarik perhatian audiens. Kata Kunci: English for specific purposes; evaluasi mata kuliah; industri kreatif; penulisan konten